First report of the ceftazidimase CTX‐M‐19 in South America. Issue 3 (22nd December 2013) - García‐Fulgueiras, V.; Bado, I.; Cordeiro, N. F.; Algorta, G.; Vignoli, R.
Abstract: We report the first detection of bla CTX‐M‐19 in South America, harboured in an Escherichia coli isolate obtained from a urine sample; such an isolate belonged to phylogenetic group A, ST603, and showed a ceftazidimase profile. bla CTX‐M‐19 was encoded in an approximately 100 kb IncI1/IncF conjugative plasmid, featuring pndAC and hok / sok addiction systems; the β ‐lactamase gene was flanked upstream by three tandem‐like transposons (IS 26, IS 10 and IS Ecp1 ), inserted one inside the other, and downstream by IS 903 .